(4+5i)(4-5i)=1

Simple and best practice solution for (4+5i)(4-5i)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4+5i)(4-5i)=1 equation:


Simplifying
(4 + 5i)(4 + -5i) = 1

Multiply (4 + 5i) * (4 + -5i)
(4(4 + -5i) + 5i * (4 + -5i)) = 1
((4 * 4 + -5i * 4) + 5i * (4 + -5i)) = 1
((16 + -20i) + 5i * (4 + -5i)) = 1
(16 + -20i + (4 * 5i + -5i * 5i)) = 1
(16 + -20i + (20i + -25i2)) = 1

Combine like terms: -20i + 20i = 0
(16 + 0 + -25i2) = 1
(16 + -25i2) = 1

Solving
16 + -25i2 = 1

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '-16' to each side of the equation.
16 + -16 + -25i2 = 1 + -16

Combine like terms: 16 + -16 = 0
0 + -25i2 = 1 + -16
-25i2 = 1 + -16

Combine like terms: 1 + -16 = -15
-25i2 = -15

Divide each side by '-25'.
i2 = 0.6

Simplifying
i2 = 0.6

Take the square root of each side:
i = {-0.774596669, 0.774596669}

See similar equations:

| 42=7x+7(-2x+18) | | 11x-23y=-5 | | (1/36)-(1/40)=(1/x) | | 4/9*7/9 | | 4/9/7/9 | | 20x^2-40x-52=0 | | 4m-12=2m-9 | | (1/36)-(1/40)=(1/t) | | (9y-8)(y+5)=(ny-2) | | 6+3x+4x= | | 4(3y-4.7)+17.4=7(4y-0.2) | | c=0.17w+0.63 | | (2x-3)+(x+5)=90 | | -4+2x=x+3 | | (2x^2+15x+21)/(x+5) | | -8(5-n)=-104 | | 8y=64.72 | | 81x^2+kx+25=0 | | 1x+3y=360 | | 6(x+4)=2x+60 | | 2x^2+9x-8=0 | | 4=8/12(-8)+b | | 2x+3x+15=20 | | -3x^2-237=0 | | M/4+4=17 | | (8m-4)/(2m-1) | | 1m+6.74+.7m=-3.8 | | -3x^2=-237 | | 3x^4-12x^3=0 | | 5d+9ford=104 | | 2(3x-5)+14=4(x+9)+4 | | 603+0.5m=16.3 |

Equations solver categories